ANALISIS PENGARUH KARAKTERISTIK PEKERJAAN, KOMPETENSI, DAN MOTIVASI TERHADAP KINERJA KARYAWAN - Dewi Meilawati, 09.05.51.0104; Waruwu, Penunjang (Students Journal of Economic and Management, 2013)
This research is a study that examined the influence of job characteristics, competence and motivation on employee performance for employees PT. Pertamina (Persero) Terminal BBM Pengapon Semarang. Research using census method where the entire population were sampled by 35 respondents. Description of the variables showed that the perception of the respondents on the variable generally high, variable job characteristics scores averaged 3.99, the variable competence scores averaged 3.60, variable motivation scores averaged 3.84, and the mean score of the variable employee performance prestudy 3.72. From the results obtained are characteristic variables does not affect the work performance of employees with a positive coefficient of 0.087 and 0.412 significance. While the competence and motivation variables have positive and significant impact on employee performance. Competence influence positive coefficient 0.418 and 0.001 significance. A positive motivational influence coefficient 0.558 and 0.000 significance. This means that the increased knowledge, skill and motivation of employees, will be able to influence employee performance.Keywords: job characteristics, competence, motivation, employee performance